Artificial Hatchery Techniques for Siamese Patin Fish (Pangasianodon hypopthalamus) at the Freshwater Aquaculture Fisheries Center, Sungai Gelam, Jambi - Ilhamdi, Ilhamdi; Suprakto, Bambang; Triyane, Viola (Department of Marine and Fisheries, Trunojoyo University of Madura, Indonesia, 2025)
ABSTRACTSiamese catfish (Pangasianodon hypopthalamus) is a type of fish that is included in the catfish group, this fish has a fairly large market so the demand for catfish is increasing from year to year. The main obstacle to the production of catfish seeds is the spawning cycle of Siamese catfish which still depends on the season, so optimization is needed in the supply of seeds through artificial spawning with the help of hormonal stimulation. This study aims to examine techniques for artificially hatching Siamese catfish using the hormone ovaprime and evaluate the performance of Siamese catfish hatcheries. The time for carrying out this research was 3 months using the observation method, participating directly in Siamese catfish hatchery techniques and through interviewing sources in the field of catfish hatchery. Siamese catfish hatchery techniques start from preparing the container, rearing the brood stock, selecting the brood stock, spawning, injecting, stripping, fertilizing, hatching, and raising the larvae until they become seeds and are ready for distribution. Based on the results of research on artificial seeding techniques for Siamese Catfish (Pangasianodon hypopthalamus) at the Gelam Jambi River Freshwater Aquaculture Fisheries Center (BPBAT), it produces an average fecundity of 170,394.75 eggs/kg. Meanwhile, the fertilization rate for four cycles averaged 69.54%, and the hatching rate was 68.95%. The problem with hatching Siamese catfish at BPBAT Sungai Gelam is that the availability of natural food is not sufficient for the needs and quantity required for larvae at the start of rearing, causing a decrease in larval survival rates.Keywords: Hatchery techniques, Siamese catfish, Pangasius hypophthalmus, artificially, seeds